Factors affecting the bioaccessibility of β-carotene in lipid-based microcapsules: Digestive conditions, the composition, structure and physical state of microcapsules. (April 2018) - Lin, Quanquan; Liang, Rong; Williams, Peter A.; Zhong, Fang
Abstract: β-Carotene is considered as a promising functional food ingredient. However, the application of β-carotene is limited by its low solubility in water, sensitivity to oxygen, light and temperature, and low oral bioavailability. Lipid-based microcapsules can be used as delivery systems to improve the bioavailability of β-carotene in addition to encapsulation and protection. This review begins by summarizing the absorption of β-carotene in lipid-based microcapsules and in vitro digestion models used in the study of β-carotene bioaccessibility. It then puts the special emphasis on the effects and potential mechanisms of simulated digestive conditions (e.g. digestive enzymes, surface-active components, mineral ions, pH, mucin, flow profiles and mechanical forces), the composition (e.g. β-carotene, oil phase, interfacial layer and gel matrix), structure (e.g. particle size, particle charge) and physical state of lipid-based microcapsules on the bioaccessibility of β-carotene during in vitro digestion. The studies presented in this review show that both the simulated digestive conditions and the characteristics (composition and structure) of lipid-based microcapsules affect the β-carotene bioaccessibility by impacting the structure stability of delivery systems, digestion of lipid and the transfer of β-carotene to mixed micelles. It can be concluded that appropriate digestive parameters should be chosen depending on the nature of the sample being tested, and that the bioaccessibility of β-carotene can be regulated by rational selection of the composition and structure fabrication of microcapsules. Such information can be used for the design of digestion models and development of β-carotene supplements with high bioavailability. Graphical abstract: Image Highlights: Metabolism of β-carotene in lipid-based microcapsules has been proposed. Effects of simulated digestive conditions on β-carotene bioaccessibility have been summarized. Effects of composition of lipid-based microcapsules on β-carotene bioacessibility have been reviewed. Effects of structure of lipid-based microcapsules on β-carotene bioaccessibility have been described. Effects of physical state of lipid-based microcapsules on β-carotene bioaccessibility have been summarized.